Exploring the psychometric properties of the Intellectual Disability versions of the Short Warwick–Edinburgh Mental Wellbeing Scale and Kidscreen10, self‐reported by adolescents with intellectual disability. Issue 5 (13th February 2023) - Davison, J.; Maguire, S.; McLaughlin, M.; Simms, V.; Bunting, B.
Abstract: Background: There are no validated self‐report measures that can be used to assess health and wellbeing in adolescents with intellectual disability (ID). Method: The aim of this study was to explore the psychometric properties of two newly adapted self‐report health‐related quality of life (HRQoL) and mental wellbeing measures: the Intellectual Disability versions of the Short Warwick–Edinburgh Mental Wellbeing Scale (ID‐SWEMWBS) and Kidscreen10 (ID‐Kidscreen10). For this, we used data from a sample of 427 adolescents (aged 11–19) with ID recruited from special school settings. Results: Confirmatory factor analysis (CFA) was conducted to validate the factor structure of both measures. Internal consistency was assessed using Cronbach's alpha and test–retest reliability was analysed using intra‐class correlation coefficients. The internal consistency measured using Cronbach's alpha was found to be in the range of 0.70–0.78, test–retest reliabilities were expressed using intra‐class correlation coefficients that were found to be high for both measures (ID‐SWEMWBS, 0.758; ID‐Kidscreen10, 0.723), and the CFA supported the unidimensional structure of both measures. Conclusions: The results of this study indicate that the ID‐SWEMWBS and ID‐Kidscreen10 have very good psychometric properties and can be used as self‐report measures to assess HRQoL and mental wellbeing in adolescents with ID.